Mapping changes in support: a longitudinal analysis of networks of pre-service mathematics and science teachers. (4th May 2018) - Bokhove, Christian; Downey, Christopher
Abstract: In England teachers of secondary school mathematics and science are in short supply and it is important to understand how pre-service teachers develop and maintain networks of support during their training year and the impact these networks can have on their training outcomes. The purpose of this study is to examine how changes to the size and composition of these support networks during the training year are associated with programme outcomes. The paper draws on social network theory to examine the nature of the support networks that develop around each pre-service teacher, and examines how supportive ties were initiated, maintained, and broken over the course of the training year. A survey design was utilised to collect data at four time points across the 2014–2015 academic year from a total cohort of more than 75 pre-service teachers. At all four time points, participants were asked to nominate those peers and others to whom they had turned during the previous month for different aspects of support. Results showed that the size and composition of support networks changed over time with significant differences in the development of the networks between pre-service teachers on school-led and university-led programmes.